The Influence of Slang on the Use of Indonesian Language at STKIP Harapan Bima Students - Supriadin, Deden (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to explain the influence of slang on the use of Indonesian by STKIP Harapan Bima students. This research is of a qualitative type because the data described are theories and environmental conditions that will be examined carefully. This research uses a qualitative descriptive method to describe the problems studied. Data Collection Techniques To collect data, the author conducted field research. Field research is research that the author carries out by making direct observations on the objects to be studied, and then collecting data and information obtained from the respondents. This data and information collection was carried out using observation, interviews, and recording. The results of this research are related to the influence of slang on the use of Indonesian. STKIP Harapan Bima students show that the use of slang itself is not an expression of love for Indonesian culture and language, but rather so that we as social creatures who cannot be separated from each other do not experience confusion or misinterpretation of the language used or spoken by another person or social group.